Effect of extended morning fasting upon ad libitum lunch intake and associated metabolic and hormonal responses in obese adults - Chowdhury, E.A.; Richardson, J.D.; Tsintzas, Kostas; Thompson, D.; Betts, J.A. (Nature Publishing Group, 2015)
Background/Objectives: